THE EFFECT OF COMIC STRIPS ON THE GRADE EIGHT STUDENTS™ READING COMPREHENSION AT SMPS PRAYATNA MEDAN - Siregar, Siti Ramlah; Sirait, Dahlia (Universitas Negeri Medan, 2023)
English is the most important subject nowadays. There are some texts which have to be mastered by junior high school students. One of the them is the narrative text, a text that tells a story, in which the social functions are to inform, entertain, or amuse the readers. students have problems and difficulty reading comprehension of story texts. They found difficulties in finding information, main ideas or intentions of sentences in the text. Besides that, their lacking of vocabulary that students have, what is contained in the contents of the reading is not conveyed to students, and students' interest and motivation towards learning English is lacking. The purpose of this research is to find out whether the Comic Strips has an effect or not siginificant reading comprehension. This research was conducted using quantitative methods. The research sample consisted of 20 students in class VIII-1 as the experimental class and 20 students in classVIII-2 as the control class. From the data that has been analyzed, the researcher found that the average result of the experimental class was 35 while the average result of the control class was 25. The results of calculations using the t test showed that t observed was higher than the t table (4.48 > 2.02) with df: 38 at the significance level a=0.025. So the alternative hypothesis (ha) is accepted and the null hypothesis is rejected. So it can be concluded that the Comic Strips in the improve reading comprehension learning process is effective to use.